Translocation and female subjectivities in four contemporary narratives : Kingston’s The woman warrior, Magona’s To my children’s children and Forced to grow and Hoffman’s Lost in translation - Joss, Elizabeth (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MA (English Studies))--University of Stellenbosch, 2009.